PEMAKNAAN JIHAD BAGI ANGGOTA FPI RIAU DALAM AKSI SUPER DAMAI 212 DI JAKARTA - Masithoh, Dewi; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Islamic Defense Action volume III (Aksi Super Damai 212) on December 2, 2016 in Monas Jakarta followed by Muslims from all over Indonesia became a historic event for the nation. Action backdrop of religion by the Governor of DKI Jakarta. The action led by GNPF-MUI with the theme "Tabligh Akbar dan Jihad Kebangsaan, Merajut Ukhuwah Islamiyah Menuju Indonesia Damai dan Berkeadilan" colored with various stories of struggle as a Muslim jihad to maintain the honor of Islam. This study aims to find out how the motives, meaning jihad and communication experience of FPI Riau members in Aksi Super Damai 212 in Jakarta.This research uses qualitative research method with phenomenology approach. The subjects consisted of five members of DPD FPI Riau Province selected by using purposive sampling technique. Data collection is done through in-depth interviews, observation and documentation. To perform the validity of data, the authors use extension opt-in techniques, observational persistence and triangulation.The result of the research shows that the motive of FPI members to follow the Aksi Super Damai in Jakarta consists of because motive which includes ghirah and persistence, obedient ulama, love of Al-Qur'an, jihad and family support and in order to motive include self introspection, law enforcement and ukhuwah Islamiyah. While the meaning of FPI members to jihad in action is divided into several categories of meaning that are (1) spiritual jihad, (2) jihad treasure, (3) jihad of soul and (4) jihad constitution which entirely boils down to jihad fi sabilillah. The communication experience of FPI members in action generates a pleasant communication experience based on their interaction with Allah (habluminallah) and interaction with fellow human beings (habluminannas) covering the interaction of fellow Muslims, non-Muslims, the security forces and the government.Keywords: defining, jihad, action 212, FPI